SYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL EVALUATION OF DIVALENT METAL COMPLEXES WITH SCHIFF BASES DERIVED FROM 4- ANISALDEHYDE AND ARGININE - Saulawa, Aisha Ibrahim; Dangani, Abdullahi Hussaini; Muhammad, Saudat (FUDMA Journal of Sciences, 2024)
In the present study, a new Schiff base, 5-Guanidino-2-[(4-methoxy-benzylidene)-amino]-pentanoic acid, and its metal (II) complexes were synthesized. Structural characterization was done using FTIR, UV-visible spectral analysis, molar conductance, and melting/decomposition temperature determination. Spectral studies revealed the ligand to be bidentate, coordinating with the metal through the carboxylic oxygen and azomethine nitrogen. The antibacterial activity (in vitro) against Escherichia coli and Staphylococcus aureus strains was studied using the agar well diffusion method. The results indicated that the free ligand exhibited no biological activity, whereas the cadmium complex (C28H38CdN8O6) proved to be the best antibacterial agent (up to 27 mm diameter inhibition zone against E. coli), followed by the Mn (II) complex and the Ni (III) complex having the least activity against both Escherichia coli and Staphylococcus aureus. This means that metal chelation significantly affected the anti-bacterial behavior of the organic Schiff base. This study contributes to the growing body of knowledge in the field of bioinorganic chemistry and may have potential implications for pharmaceutical and biomedical applications.
Keywords: Antibacterial activity; Schiff base; FTIR; Complexes